Management of hypertension in Nigeria: The barriers and challenges - Oguanobi, Nelson I (Journal of Cardiology and Cardiovascular Medicine, 2021)
In recent years there has been increasing concern about the growing burden of cardiovascular disease (CVD) in developing countries. Systemic hypertension remains the commonest form of CVD and is identified as a key modifiable risk factor for cardiovascular morbidity and mortality. Primary and secondary prevention of cardiovascular adverse events are public health priorities. This review highlights the potential barriers and challenges to hypertension care in Africa’s most populous country, Nigeria, and proffers relevant recommendations.